Perlindungan Hukum Pekerja Perempuan Di Malam Hari Dalam Perspektif UU 13 Tahun 2003 - Muslim, Bayu (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2020)
The worker as workers in companies are still subjected to discriminatory treatment from employers, such as the rights that should be received by women workers such as protection of safety, health to work at night. Not only in the work rules, the rights and obligations of women workers are listed in the work agreement, but the protection of women workers has been regulated in the law. Law No. 13 of 2003 and the Minister of Energy and Transmigration Ministerial Decree No. Kep. ​​224 / Men / 2003. That in the two regulations, regulates how to protect women workers who work at night. Where there are provisions and obligations of employers who employ women workers or workers at night to comply. Supervision of the legal protection of women workers for the realization of the application of laws relating to workers and companies carried out by the government or labor agencies both at the center and in the regions. With the legal protection of women workers who work at night is expected to be increasingly protected their rights. keywords: legal protection, women workers, nighttime.